Strategies for Diversifying the Pool of Graduate Students in Biomedical Sciences - Coronado, Gloria D. (2012)
As part of our National Cancer Institute–sponsored partnership between New Mexico State University and the Fred Hutchinson Cancer Research Center, we implemented the Cancer Research Internship for Undergraduate Students to expand the pipeline of underrepresented students who can conduct cancer-related research. A total of 21 students participated in the program from 2008 to 2011. Students were generally of senior standing (47%), female (90%), and Hispanic (85%). We present a logic model to describe the short-term, medium-term, and long-term outputs of the program. Comparisons of pre- and post-internship surveys showed significant improvements in short-term outputs including interest (p<0.001) and motivation (p<0.001) to attend graduate school, as well as preparedness to conduct research (p=0.01) and write a personal statement (p=0.04). Thirteen students were successfully tracked, and of the 9 who had earned a bachelor’s degree, 6 were admitted into a graduate program (67%), and 4 of these programs were in the biomedical sciences.